Pelatihan Pembuatan Block Compost Menggunakan Variasi Bahan Organik Dari Limbah Teh Hijau - Selviana Selviana; Muriani Nur Hayati; Budi Widiyanto (Jurnal Pemberdayaan Masyarakat, 2023)
The training on the production of block compost using various organic materials derived from green tea waste offers a sustainable solution for waste management. This study focuses on the creation of compost blocks, utilizing organic matter from green tea waste, with keywords including compost block, organic materials, and green tea waste. The training encompasses the identification of suitable organic components, the composting process, and the advantages of compost blocks. By integrating waste recycling, the initiative not only reduces waste, specifically green tea waste, but also provides an eco-friendly approach to enhancing soil fertility and plant growth. The training underscores the importance of sustainable waste management, promoting environmentally friendly practices, and supporting the principles of the Sustainable Development Goals (SDGs).